Presepsi Konsumen Pada Makanan Tradisional Cassava Leaf Dendeng - Dea Namira; Hijriyantomi Suyuthie (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This research began when the researchers offered traditional food product "Cassava leaf dendeng" to tourists, while introducing a new innovation from the creativity of the local community. "Cassava leaf dendeng" originates from South Solok. However, when offering the product, none of the tourists were interested in trying it because they couldn't imagine the taste of "Cassava leaf dendeng". Through this research, the researchers aimed to understand consumers' perceptions of the traditional food "Cassava leaf dendeng”. This research is of descriptive type. The sample in this research consists of ten individuals, selected with a distribution of three culinary teachers, four tourists from North Sumatra, and three local residents. Data collection was carried out using purposive sampling, and the data was collected through observation, interviews, and documentation. The results of this research indicate that "Cassava leaf dendeng" with a dark green color is more preferred, and the flattened shape results in a crunchier texture. A milder aroma of "Cassava leaf dendeng" is more appealing. The seasoning used in "Cassava leaf dendeng" is savory and sweet, but it would be even better when served with sambal.